Studying the Effect of Bacillus Subtilis Suspension on Plant Height, Weight and Number of Potato Tubers - Khalil, Anwar Mohammed; Ahmed , Abd Almonem; Hasan, Marwan Abdo (Al-Mustansiriyah Journal of Science, 2024)
Background: Bacillus subtilis is one of the microorganisms widely spread in soil. It is characterized by broad activity in producing many metabolites that play an important role against many plant pathogens. In addition, it contributes to increasing the production of plant hormones and facilitating the absorption of many important elements, which reflects positively on the growth and productivity of the plant. Objective: This study aims to investigate the effect of Bacillus subtilis treatment on plant height, weight, and number of potato tubers. Methods: A suspension of Bacillus subtilis was tested over three intermittent periods on plant height and its yield (weight and number of tubers) of the Afamia potato plant compared with the control on two lines of potato without treatment. Results: The relative increase in the average longitudinal growth of the plants in the second line was 49.75% compared to the first line, 29.53%. The average number and weight of tubers were calculated for each replicate of the first-line plants (sprayed with water only), and then the average was calculated for each replicate of the second-line plants (sprayed with bacteria). The average number of tubers in the plants treated with bacteria was 17.56 tubers compared to its counterparts sprayed with water only. In terms of the number of tubers, which amounted to 15 tubers, we obtained a percentage increase of 17.06%. In contrast, the average weight of the tubers was 1618.4 grams compared to its counterpart sprayed with water only, which amounted to 897.6 grams, and thus we obtained a percentage increase of 80.30%. Conclusions: The results showed a positive effect of using Bacillus subtilis on plant height and the number and weight of potato tubers compared to the control. This was explained by the fact that Bacillus Subtilis stimulated the plant’s resistance to pathogens and improved plant growth through the production of hormones and facilitating the assimilation and absorption of nutrients.